B2 or Not B2: A Systematic Literature Review on Migraine Headaches and Riboflavin Deficiency - Varkey, Thomas; Farhat, Jordan; Tobin, Joshua (Headache Medicine, 2023)
Objective To assess the prevalence of riboflavin deficiency in patients with migraines or headaches. Methods Systematic review of the literature following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results Two articles met the inclusion and exclusion criteria, and neither of these discussed riboflavin deficiency prevalence in those patients who suffer from migraines. Conclusion The prevalence of riboflavin deficiency in migraineurs and in headache patients is unknown.